Asia-Pacific strategic relations seeking convergent security - Tow, William T. (Cambridge University Press, 2001)
"This comprehensive book is an overview of security issues in the Asia-Pacific and an argument for a strategy that promises to achieve greater regional stability. It finds that current approaches by policy-makers increase the likelihood of conflict. Instead, it proposes that a strategy of 'convergent security' be adopted to build an enduring regional security framework. A concise survey of key policy approaches to regional security politics, Asia-Pacific Strategic Relations also includes extensive historical and contemporary empirical discussion. This authoritative and broad-ranging survey is designed for a wide body of analysts and students of the problems of contemporary Asian politics and strategy."--BOOK JACKET.